The Influence of Brand Page Commitment and brand awareness on puchase Interest Mediated by word of mouth on product brands advertised and social media - Nurfauzia, Fadila; Karmila, Ila; Sidik, Fadel Muhammad (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
Advertisement is a promotional tool in introducing and developing a product to make consumers or potential buyers aware of the existence and advantages of the product offered (Dewi et al., 2012). The purpose of this study was to analyze the influence of Brand Page Commitment and Brand Awareness on Purchase Interest Mediated by Word of Mouth on Product Brands Advertised on social media. This study is a quantitative study. The results and discussions obtained are that brand page commitment has a positive and significant effect on word of mouth on product brands advertised on social media among students of Jenderal Achmad Yani University, Brand awareness has a positive and significant effect on word of mouth on product brands advertised in the media among students of Jenderal Achmad Yani University, brand page commitment has a positive and significant effect on purchase interest in product brands advertised on social media. Among students of Jenderal Achmad Yani University, brand awareness does not affect purchase interest in product brands advertised on social media. Among students of Jenderal Achmad Yani University, brand page commitment has a positive and significant effect on purchase intention mediated by word of mouth on product brands advertised on social media. Among students of Jenderal Achmad Yani University, brand awareness has a positive and significant effect on purchase intention. mediated by word of mouth on product brands advertised on social media among students of Jenderal Achmad Yani University